2010
DOI: 10.1007/s10763-010-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mathematics Achievement: The Influence of Prior Achievement and Attitudes

Abstract: Achievement in mathematics is inextricably linked to future career opportunities, and therefore, understanding those factors that influence achievement is important. This study sought to examine the relationships among attitude towards mathematics, ability and mathematical achievement. This examination was also supported by a focus on gender effects. By drawing on a sample of Australian secondary school students, it was demonstrated through the results of a multivariate analysis of variance that females were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 24 publications
2
53
0
10
Order By: Relevance
“…Frenzel, Pekrun and Goetz, with a sample of 5th grade students, found that girls reported significantly more anxiety, hopelessness and shame, and less enjoyment and pride than boys [22]. In contrast to those studies, there are some other studies which suggest that females are more likely to hold positive attitudes toward mathematics or perceived mathematics as more important than males [23] [24]. However, there are many studies suggest that there is no significant difference between attitude towards mathematics among different gender students [3] [4] [5] [25].…”
Section: Student Attitudes Toward Mathematicsmentioning
confidence: 93%
“…Frenzel, Pekrun and Goetz, with a sample of 5th grade students, found that girls reported significantly more anxiety, hopelessness and shame, and less enjoyment and pride than boys [22]. In contrast to those studies, there are some other studies which suggest that females are more likely to hold positive attitudes toward mathematics or perceived mathematics as more important than males [23] [24]. However, there are many studies suggest that there is no significant difference between attitude towards mathematics among different gender students [3] [4] [5] [25].…”
Section: Student Attitudes Toward Mathematicsmentioning
confidence: 93%
“…In the same way, students' views on usefulness and significance of mathematics are related to their mathematics performance (Kiwanuka et.al, 2017). Hemmings et al (2011) found prior achievement and attitudes towards mathematics to be highly predictive of student performance. The study of Mata, Monterio and Peixoto (2012) highlighted the effect of mathematics achievement and grade level on positive attitude towards mathematics.…”
Section: Introductionmentioning
confidence: 91%
“…All of these data, when compared to the results of the other analyses, indicated that this variable had more predictive power than any other individual variable except for unweighted high school GPA. That supported studies from the literature that have found students' high school math preparation to be a significant factor for predicting success in college math courses (Hemmings et al, 2011;Kessel & Linn, 1996;Levin & Wyckoff, 1991;Sadler et al, 2012;Veenstra et al, 2008). Since the statistics for the overall model of predictors indicated that this predictor variable was not significant (Wald = 2.764, p = .096), we must fail to reject this null hypothesis.…”
Section: Null Hypothesissupporting
confidence: 74%
“…A study involving college students in Australia concluded that both prior math achievement and attitude toward math were highly predictive of later success (Hemmings, Grootenboer, & Kay, 2011). According to Kessel and Linn (1996), both previous grades and entrance exams (i.e., SAT) significantly predict success in college math courses.…”
Section: Predicting Success In Stem and Mathematicsmentioning
confidence: 99%